Determinação de constituintes inorgânicos em tabacos por espectrometria de absorção atômica com chama e forno tubular na chama e aerossol térmico. - Frank Pereira de Andrade (2008)
It was evaluated sample pretreatment procedures for Cd, Cu, Fe, Mn, Pb, and Zn determination in tobacco samples. Extraction and digestion procedures were investigated as alternative to the classic decomposition sample pretreatment. With the goal to became faster the sample preparation procedures, in this work, the extraction and digestion assisted by microwave radiation and the extraction assisted by ultrasonic radiation were used for Cu, Fe, Mn and Zn determination in different tobacco samples: roll tobaccos, straw cigarettes and commercialcigarettes. Total teor was obtained after ash and wet decomposition applying muffle furnace. The efficiency of each investigated procedure was done comparing the values with the total teor. Elemental determination was realized by flame atomic absorption spectrometry (F AAS). Copper, Fe, Mn, and Zn concentration were dependent of tobacco type. The roll tobacco presented the highest values. When compared to the total teor, Zn was the element less extracted in all procedures, with values minor than 30%, suggesting that this metal is more strongly linked to the organic matrix. The efficiency of the procedures assisted by ultrasonic radiation was inferior when comparing to the procedures assisted by microwave radiation. For Cd and Pb, whose teor werebelow of the limits of detection of the F AAS technique, it was developed a preconcentrated and cloud point extraction (CPE) procedure. The studied variables were: hydrophobic complexing agents type: PAR or Br-PADAP, volume of the solution 10-3 mol L-1 of complexing agents, pH and volume of solution 5% m/v of Triton X-114. The different tobacco samples were digested employing ash and wet procedure and the colourless solution was submitted to CPE procedure. The determinations were accomplished by thermospray flame furnace atomic absorption spectrometry (TS-FF-AAS), using air as carrier. The Br-PADAP wasthe best complexing agent for the both elements, and the pH was adjusted to 9.